Model kompetencji menedżera w nowoczesnej organizacji: Model of competence of the manager in the modern organization - Załoga, Wiesława (Management and Administration Journal, 2021)
Managing a modern company requires a good and professional management, and therefore management especially in today's space devoted to managerial competence. The issue of the competence of the manager in the organization of the future is a factor leading to a dynamically changing environment. Managerial competence is the sum held by the abilities, skills and knowledge supported by the relevant personality traits, experiences, behaviors and procedures of the employee. Competencies are closely related to professional practice and professional development (learning during practical activities, using feedback from the successes and failures). Competence refers to the activities of organizations or people. In the case of the organization's competence is meeting such as educational needs, providing products and services of the highest quality. In the case of competence relating to people, a person is competent in the performance of such an act. Competencies include specific and general items (training and station).results than on the process, which means that when they acquire and develop the greatest emphasis is placed on the results. Competence development is a permanent part of the work, not the additional element. The development is oriented on the unit, because it is based solely on the results achieved by it. Competence development is compatible with the process of learning in the long term, and its specific phases. Favored by new responsibilities, challenges and failures that motivate to acquire new skills. The basis for the development of new competences is openness to experience, self-reflection and the ability to learn from their mistakes and successes. The purpose of this article is to present a model of competence manager in the modern organization, with particular emphasis on the components included in the competence based on the selected company. The article presents the current and postulated manager competency model in modern organization in the light of their own study based on selected company.